Acute Essex-Lopresti Syndrome: About a Case of Brachioradialis Tendon Transfer - Charlotte, Gabriel; Honecker, Sophie; Xavier, Fred; Facca, Sybille; Lazarus, Priscille; Liverneaux, Philippe (Journal of Wrist Surgery, 2021)
Background The classic treatment for acute Essex-Lopresti syndrome is closed reduction percutaneous pinning (CRPP) of the distal radioulnar joint (DRUJ). This work aimed to verify whether it was possible to add a transfer of the brachioradialis tendon to the pinning.Case Description The patient was a 39-year-old right-handed man, climbing instructor, who sustained the Mason II fracture and disjunction of the DRUJ. A transfer of the brachioradialis tendon severed from its muscle attach that was made through a bone tunnel passing through the radius and the neck of the ulna. The clinical and radiological result at the 6-month follow-up was satisfactory.Literature Review and Clinical Relevance Our results in a single case showed that the brachioradialis tendon transfer was useful in acute Essex-Lopresti syndrome.
Keywords: brachioradialis; distal radioulnar joint; Essex-Lopresti syndrome; Mason's fracture; tendon transfer